2019
DOI: 10.1002/jcp.28103
|View full text |Cite
|
Sign up to set email alerts
|

Impact of curcumin on toll‐like receptors

Abstract: Toll‐like receptors (TLRs) have a pivotal role in the activation of innate immune response and inflammation. TLRs can be divided into two subgroups including extracellular TLRs that recognize microbial membrane components (TLR1, 2, 4, 5, 6, and 10), and intracellular TLRs that recognize microbial nucleic acids (TLR3, 7, 8, and 9). Curcumin is a dietary polyphenol from Curcuma longa L. that is reputed to have diverse biological and pharmacological effects. Extensive research has defined the molecular mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 132 publications
(217 reference statements)
2
32
0
2
Order By: Relevance
“…Treatments abrogating TLR4-dependent signal transduction have been shown to lead to an amelioration of intestinal inflammatory disease [268]. Curcumin has been shown to inhibit both MyD88-dependent and -independent signaling mechanisms [88,269]. Additionally, curcumin can bind to myeloid differentiation protein 2 (MD-2), a protein bound to the extracellular TLR4 domain, thereby suppressing the innate immune response to LPS [270].…”
Section: The Effects Of Curcumin On Intestinal Inflammatory Diseasesmentioning
confidence: 99%
“…Treatments abrogating TLR4-dependent signal transduction have been shown to lead to an amelioration of intestinal inflammatory disease [268]. Curcumin has been shown to inhibit both MyD88-dependent and -independent signaling mechanisms [88,269]. Additionally, curcumin can bind to myeloid differentiation protein 2 (MD-2), a protein bound to the extracellular TLR4 domain, thereby suppressing the innate immune response to LPS [270].…”
Section: The Effects Of Curcumin On Intestinal Inflammatory Diseasesmentioning
confidence: 99%
“…[ 30 32 ] In AP-1 signaling, curcumin can inhibit MAPK, ERK1/2, JNK, and p38, both directly and indirectly, thereby limiting transcription of inflammatory target genes. [ 33 ] We hope this systematic review will provide more reliable evidence in the management of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal inflammation is a complex process, and TLR4 signalling pathway plays an important role in the inflammatory process (Płóciennikowska, Hromada-Judycka, Borzęcka, & Kwiatkowska, 2015). Previous studies revealed that emodin and curcumin could attenuate inflammatory responses through directly suppressing TLR4 signalling pathway (Boozari, Butler, & Sahebkar, 2019;Ding et al, 2018;Fu et al, 2014;Zhu et al, 2012).…”
Section: F I G U R Ementioning
confidence: 99%